2014
DOI: 10.1016/j.jcp.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling gamma-ray photon emission and pair production in high-intensity laser–matter interactions

Abstract: In high-intensity (> 10 21 Wcm −2 ) laser-matter interactions gamma-ray photon emission by the electrons can strongly effect the electron's dynamics and copious numbers of electron-positron pairs can be produced by the emitted photons. We show how these processes can be included in simulations by coupling a Monte-Carlo algorithm describing the emission to a particle-in-cell code. The Monte-Carlo algorithm includes quantum corrections to the photon emission, which we show must be included if the pair production… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
394
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(400 citation statements)
references
References 55 publications
(75 reference statements)
6
394
0
Order By: Relevance
“…It does this by factorizing the cascade into a product of first-order processes (nonlinear Compton scattering and Breit-Wheeler pair creation), which occur along the particle trajectory at locations pseudorandomly determined according to the appropriate LCFA probability rate. (See [45,46] for detailed discussion of this 'QED-PIC' concept. )…”
Section: The Positron Yield and Optimal Target Thicknessmentioning
confidence: 99%
“…It does this by factorizing the cascade into a product of first-order processes (nonlinear Compton scattering and Breit-Wheeler pair creation), which occur along the particle trajectory at locations pseudorandomly determined according to the appropriate LCFA probability rate. (See [45,46] for detailed discussion of this 'QED-PIC' concept. )…”
Section: The Positron Yield and Optimal Target Thicknessmentioning
confidence: 99%
“…This is confirmed by using three-dimensional QED particle-in-cell (PIC) simulations based on code EPOCH [34,35], which includes QED effects to deal with the quantum radiation. It has been found that the OAM of high energy gamma-ray photons is transferred from the spin angular momentum (SAM) and OAM of the driving laser.…”
mentioning
confidence: 78%
“…In line with the current understanding of high-intensity laser matter interactions in the quantum regime, we model photon emission as a succession of incoherent one-photon events [17,[25][26][27]. There will be regimes where this assumption becomes challenged, for instance when extreme field strengths are reached such that αχ 2=3 ≳ 1.…”
mentioning
confidence: 99%
“…For these codes to be used for depletion calculations, each Compton process needs to be characterized by photon energy, angle of emission, and the number of absorbed photons. Furthermore, in numerical (QED-particle-in-cell) simulations of multistage emission processes, which lead to the formation of avalanches or cascades, photon and electron emission angles strongly determine the probability of the subsequent pair production or photon emission process, respectively [4,17,25,27,30,31]. We hence proceed by calculating these quantities.…”
mentioning
confidence: 99%